The Differences In The Quality Of Mixed Material Radiation Aprons At Dr. Moewardi Hospital With A Review Of Attenuation Coefficient Analysis - Alviana Hapsari Purbarani; Umaimah, Umi; Eka Prasetya, Firman (Indonesian Basic and Experimental Health Sciences, 2025)
IntroductionRadiation aprons are essential protective equipment in radiology, and the Regulation of the Head of BAPETEN No. 4 of 2020 requires aprons in Diagnostic and Interventional Radiology units to provide protection equivalent to 0.25 mmPb, 0.35 mmPb, or 0.5 mmPb. This study aimed to evaluate the quality of mixed-material radiation aprons at Dr. Moewardi Hospital by analyzing their attenuation coefficients. MethodsThis study assessed several apron brands available in the Radiology Installation and Cathlab Unit. Measurements were performed using a GE Proteus X-ray machine and a Raysafe X-ray Multimeter Detector. The X-ray parameters were set at 100 kV, 10 mAs, 100 cm tube-to-detector distance, and a 5 × 5 cm irradiation field, with variations in apron thickness. The reference attenuation coefficient of Pb under the same parameters was calculated as 6.32 mm⁻¹. Apron brands tested included Primax 0.35 mmPb, ProteX 0.5 mmPb, Infab 0.25 mmPb, Lead X 0.25 mmPb, Rayshield 0.25 mmPb, Xenolite 0.35 mmPb, and Trucomfii 0.5 mmPb. Results The attenuation coefficients obtained were 4.67 mm⁻¹, 4.49 mm⁻¹, 4.476 mm⁻¹, 3.94 mm⁻¹, 3.04 mm⁻¹, 2.63 mm⁻¹, and 2.22 mm⁻¹, respectively. The highest coefficient was observed in the Lead X 0.25 mmPb apron. All apron attenuation coefficients were lower than the Pb reference value. ConclusionAll mixed-material aprons evaluated demonstrated lower attenuation coefficients compared with pure Pb under identical exposure conditions. These findings indicate variability in protective performance across brands, highlighting the need for routine quality assessment to ensure compliance with regulatory requirements.